Electronic Blood Donation Portal - Elhejaazi, Balqees (Libyan International Medical university "Faculty of Information Technology", 2018)
advertisements are frequently seen on social Blood Donation and Blood Transfusion Services (BTS) are crucial for saving people’s lives. Recently worldwide efforts have been undertaken to utilize social media and smartphone applications to make the blood donation process more convenient, offer additional services, and create communities around blood donation centers. Blood banks suffer frequent shortage of blood hence, networks urging healthy individuals to donate blood for patients who urgently require blood transfusion.